Extralinguistic Analysis of Phraseologisms. (Texas Journal of Philology, Culture and History, 2023)
In this article, the phraseology of the Uzbek and French peoples, the views of linguists have been studied and, to one degree or another, analyzed and compared. The phrases used to enrich the language used in the speech process were translated into Uzbek and commented on.